Evaluating website performance as a digital awareness tool for cultural festivals: A google analytics study of festival Golo Koe - Fitri Ciptosari; Engelbertus Vione; Teddy Halim (Universitas Merdeka Malang, 2026)
The development of digital technology has transformed the way cultural festivals communicate with potential visitors, positioning websites as strategic tools for building digital awareness. While previous studies have primarily focused on website quality and user satisfaction, limited research has examined how behavioral analytics data can be used to evaluate the role of cultural festival websites in generating digital awareness. This study aims to evaluate the performance of the Golo Koe Festival website as a digital awareness tool for a cultural festival using Google Analytics data. A descriptive quantitative approach with a case study method was employed. The research analyzed website traffic performance, top pages, traffic sources, and audience demographics based on Google Analytics data collected from 1 June to 31 August 2025. The findings show that the website attracted 824 new users out of 825 active users, indicating its effectiveness in reaching previously unreached audiences. Organic search was the dominant traffic source (64.3%), followed by Instagram referrals (16.0%), demonstrating the important role of search engines and social media in generating digital awareness. However, the average engagement time was relatively short (41 seconds), and the homepage recorded a high bounce rate (56%), suggesting that while the website successfully attracted audience attention, it was less effective in encouraging deeper content exploration. Audience demographics revealed that visitors were predominantly domestic, although the presence of international users indicated emerging global interest in the festival. This study concludes that website performance should be evaluated through both awareness indicators and engagement indicators. The findings contribute to digital tourism marketing literature by demonstrating how behavioral analytics can be used to assess digital awareness in cultural festival promotion and provide practical insights for optimizing data-driven strategies to support sustainable cultural tourism development.